2010
DOI: 10.1158/1078-0432.ccr-09-1766
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-Activated Protein/Extracellular Signal-Regulated Kinase Kinase Inhibition Results in Biphasic Alteration of Epidermal Homeostasis with Keratinocytic Apoptosis and Pigmentation Disorders

Abstract: Purpose: Raf/mitogen-activated protein/extracellular signal-regulated kinase (ERK) kinase (MEK)/ERK signaling pathway is constitutively activated in melanoma. AZD6244 blocks MEK1/2, inhibiting ERK phosphorylation. We focus on associated cutaneous toxicity and we attempt to understand the underlying pathophysiology and design treatment strategies.Experimental Design: Dermatologic conditions of 22 patients with unresectable melanoma stage III/ IV in a phase II trial were evaluated. Thirteen patients received AZD… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 28 publications
(37 reference statements)
2
37
0
Order By: Relevance
“…Similarly a stress reaction and disturbance of homoeostasis in the skin and finally chronic changes have been shown [14]. Our findings suggest partial resolution of the retinal thinning after end of treatment.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Similarly a stress reaction and disturbance of homoeostasis in the skin and finally chronic changes have been shown [14]. Our findings suggest partial resolution of the retinal thinning after end of treatment.…”
Section: Discussionsupporting
confidence: 77%
“…Moreover, MEK inhibitors have demonstrated activity in NRAS mutated melanoma as well [2]. Common MEK inhibitor-related adverse events include acneiform skin rash, oedema, retinopathy and diarrhoea [14,15]. Using combined therapy regimens many adverse events observed in BRAF monotherapy disappear or decrease in frequency.…”
Section: Introductionmentioning
confidence: 99%
“…The most common adverse events were rash (63%–74% of patients) and fatigue (41%–68% of patients) in a dose-dependent manner in phase 1 studies 32,33. Selumetinib-induced skin reactions have been evaluated in patients with advanced melanoma in a phase 2 study 58. The most common acute skin reaction was papulopustular rash on the face, upper chest, and back with increased apoptotic keratinocytes and focal neutrophil infiltration histologically.…”
Section: Selumetinib In Specific Populationsmentioning
confidence: 99%
“…16 It interferes with epidermal homeostasis. 18 In a phase 2 clinical trial, AZD6244 showed similar efficacy with respect to progression-free survival as control treatment. 19 In a phase 2 clinical trial of 200 patients with melanoma patients, AZD6244 monotherapy resulted in lasting remissions, mainly in patients with documented BRAF mutations.…”
Section: Introductionmentioning
confidence: 97%